Nucleus tractus solitarii is required for the development and maintenance of phrenic and sympathetic long-term facilitation after acute intermittent hypoxia - Ostrowski, Daniela; Heesch, Cheryl M.; Kline, David D.; Hasser, Eileen M. (Frontiers in Physiology, 2023)
Exposure to acute intermittent hypoxia (AIH) induces prolonged increases (long term facilitation, LTF) in phrenic and sympathetic nerve activity (PhrNA, SNA) under basal conditions, and enhanced respiratory and sympathetic responses to hypoxia. The mechanisms and neurocircuitry involved are not fully defined. We tested the hypothesis that the nucleus tractus solitarii (nTS) is vital to augmentation of hypoxic responses and the initiation and maintenance of elevated phrenic (p) and splanchnic sympathetic (s) LTF following AIH. nTS neuronal activity was inhibited by nanoinjection of the GABAA receptor agonist muscimol before AIH exposure or after development of AIH-induced LTF. AIH but not sustained hypoxia induced pLTF and sLTF with maintained respiratory modulation of SSNA. nTS muscimol before AIH increased baseline SSNA with minor effects on PhrNA. nTS inhibition also markedly blunted hypoxic PhrNA and SSNA responses, and prevented altered sympathorespiratory coupling during hypoxia. Inhibiting nTS neuronal activity before AIH exposure also prevented the development of pLTF during AIH and the elevated SSNA after muscimol did not increase further during or following AIH exposure. Furthermore, nTS neuronal inhibition after the development of AIH-induced LTF substantially reversed but did not eliminate the facilitation of PhrNA. Together these findings demonstrate that mechanisms within the nTS are critical for initiation of pLTF during AIH. Moreover, ongoing nTS neuronal activity is required for full expression of sustained elevations in PhrNA following exposure to AIH although other regions likely also are important. Together, the data indicate that AIH-induced alterations within the nTS contribute to both the development and maintenance of pLTF.